The Use of Blockchain Technology in Agriculture - Aldag, Mustafa Cem (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: This paper explores the use of blockchain technology in agriculture and agricultural products.Research Design & Methods: The article is based on a critical analysis of the literature with a view to understanding the current state of use of blockchain technology in agriculture. It was assumed that blockchain technology is used in the agricultural sector to promote food security, prevent food fraud and verify the origin and authenticity of agricultural products and agricultural inputs.Findings: Blockchain technology improves traceability and transparency, allowing parties within the agricultural value chain to identify faulty or suboptimal processes as well as bad actors. This ensures that ideal conditions are pursued from farm to market. The ability to trace the origin of food products is essential when food safety breaks down. The early identification of the origin of contamination will enable food companies to swing into action quickly to prevent illness and thus save lives. Such a timely response will also help limit food wastage and will save money by containing financial fallout.Implications / Recommendations: Blockchain technology has strong potential for success within the agricultural sector. It can be used to ensure food safety by enabling the source of agricultural products, as well as the source of their potential contamination, to be traced, and the authenticity of farming inputs to be verified. Blockchain can also be employed in the process of disbursing subsidies to farmers to ensure that they benefit from subsidy programmes. Finally, blockchain technology will offer farmers better prices and better payment methods and solve challenges in land title sales and purchase registration.Contribution: Blockchain is a new technology to the agricultural sector, and enormous challenges remain. There is still no established system to regulate blockchain transactions. Nevertheless, the application of blockchain in agriculture holds promising rewards.